Factors Affecting The Failure And Success Of Online Learning In Samarinda - Ramadiani, Ramadiani; Azainil, Azainil; Khairina, Dyna Marisa; Jundillah, Muhammad Labib (EARR (Educational Administration Research and Review), 2021)
This study aims to determine the implementation of online learning at schools and colleges in Samarinda, as well as what factors become obstacles and influence the success of online learning. With the COVID-19 pandemic, schools, teachers and local governments are required to be more active, creative, and concerned about evaluating learning models and distance learning readiness, either through LMS, online learning, mobile learning, blended or hybrid learning. This study uses literature reviews, observations, questionnaires and field interviews to collect relevant data from various sources of respondents. Based on the research results, there are several problems with distance education, including; readiness of students, readiness of parents, readiness of schools, and readiness of internet facilities. The other supporting variables in this study are; age, motivation to learn, educational background, ease of application, user psychology, and learning support facilities. The data processing method uses the Structural Equation Model and Descriptive Statistics using the Lisrel and SPSS applications. The place where this research was conducted was Public School and University, namely Junior High School 1, Senior High School 2, Senior high school 3 and Mulawarman University with a total of 186 respondents. The result of this research is that Samarinda is quite ready to implement online learning, with 10 recommended benefits and obstacles that still need to be fixed.